Physical and Chemical Properties of Some Seed and Kernel Oils - Musa Ozcan, Mehmet; Endes, Zuleyha; Er, Fatih (Asian Journal of Chemistry, 2010)
Nine varieties of the seed and oils (flax, soybean, rice bran, peanut, grape, sesame, almond, sorghum, pistachio) were carried out for a comparative results on their physico-chemical and nutrition value. The oil content of oils ranged from 13.7 % (rice bran) to 53.7 % (almond). The protein contents varied between 9.7 % (sorghum) to 22.3 % (peanut). Seeds were evaluated for oil, protein, crude ash and crude fibre. Refraxtive index, relative density, unsaponifiable matter, peroxide value, saponification value and pH values were determined in the seed oils. The main fatty acids identified by gas chromatography were palmitic acid, oleic acid and linoleic acid. The oleic acid content of oils were found high compared with other acids.